(untitled) (Salam International Academic Journal, 2024)
Foreign investment, a key driver of economic growth, is significantly influenced by political and legal factors. This research paper studies and analyzes the factors affecting the attraction of foreign investment, with a particular focus on political and legal aspects. First, it introduces key concepts, such as capital, investor, and investment. Next, various factors influencing investment are examined, with an emphasis on political factors—such as political stability and government policies—and legal aspects, including the legal system and commercial laws. The paper explores how these factors impact foreign investors’ decision-making. The research findings indicate that a stable and favorable political and legal environment can considerably facilitate the attraction of foreign investment, whereas instability and inadequate laws can deter this process. Ultimately, the paper aims to provide solutions for enhancing the environment for foreign investment and facilitating the process in developing countries.